2013
DOI: 10.1371/journal.pone.0081916
|View full text |Cite
|
Sign up to set email alerts
|

Source-Sink Estimates of Genetic Introgression Show Influence of Hatchery Strays on Wild Chum Salmon Populations in Prince William Sound, Alaska

Abstract: The extent to which stray, hatchery-reared salmon affect wild populations is much debated. Although experiments show that artificial breeding and culture influence the genetics of hatchery salmon, little is known about the interaction between hatchery and wild salmon in a natural setting. Here, we estimated historical and contemporary genetic population structures of chum salmon (Oncorhynchus keta) in Prince William Sound (PWS), Alaska, with 135 single nucleotide polymorphism (SNP) markers. Historical populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 46 publications
(49 reference statements)
4
22
0
Order By: Relevance
“…Our results therefore demonstrate that straying and subsequent gene flow from hatchery releases have reduced the genetic divergence among remaining wild Atlantic salmon populations in the Gulf of Finland. Similar alterations of genetic structure due to unidirectional gene flow from reared conspecifics as a result of straying (Vasem€ agi et al 2005a;Jasper et al 2013), direct stocking (Hansen 2002;Eldridge et al 2009;Lamaze et al 2012;Marie et al 2010;Perrier et al 2013) or farm escapes (Skaala et al 2006;Bourret et al 2011;Glover et al 2012) have also been observed in earlier studies on Atlantic salmon and other salmonids.…”
Section: Temporal Changes Of Genetic Variation and Structuresupporting
confidence: 73%
See 4 more Smart Citations
“…Our results therefore demonstrate that straying and subsequent gene flow from hatchery releases have reduced the genetic divergence among remaining wild Atlantic salmon populations in the Gulf of Finland. Similar alterations of genetic structure due to unidirectional gene flow from reared conspecifics as a result of straying (Vasem€ agi et al 2005a;Jasper et al 2013), direct stocking (Hansen 2002;Eldridge et al 2009;Lamaze et al 2012;Marie et al 2010;Perrier et al 2013) or farm escapes (Skaala et al 2006;Bourret et al 2011;Glover et al 2012) have also been observed in earlier studies on Atlantic salmon and other salmonids.…”
Section: Temporal Changes Of Genetic Variation and Structuresupporting
confidence: 73%
“…; Jasper et al . ). However, it is not always the case, as hatchery fish may carry unique alleles not observed in wild populations (Verspoor ); thus, hatchery releases may also increase the genetic variability of wild populations, particularly if the source populations for hatchery stocks are larger than the wild populations.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations